Method for preparing cobalt-manganese oxide material by utilizing cobalt-doped induced crystal transformation and application of cobalt-manganese oxide material
Through cobalt doping induced crystal transformation and hydrothermal reaction, spherical cobalt-manganese oxides were prepared, which solved the problem of poor performance of manganese oxide materials, achieved supercapacitance performance improvement and environmentally friendly and efficient production, suitable for large-scale applications.
Patent Information
- Application Number
- CN202411150317.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-21
- Publication Date
- 2024-12-17
AI Technical Summary
The performance of existing manganese oxide materials in supercapacitors is limited by low specific surface area, poor electron and ion conduction properties and dissolution problems during cycling, resulting in a large gap between them and the theoretical capacity, high manufacturing costs and strict environmental pollution. .
Through cobalt doping, spherical cobalt-manganese oxides are prepared by hydrothermal reaction and under-air calcination. The crystal forms are controlled to be Mn2O3, Mn3O4 and CoMnO3 to avoid the use of potassium permanganate, and glucose-polyvinyl alcohol complexing is used. As a modifier, the material can improve the conductivity and specific capacitance of the material.
The supercapacitance performance of manganese oxide materials has been improved, which reduces manufacturing costs and environmental pollution. The material process is simple and controllable, suitable for mass production, and avoids the dissolution of nanostructures in the electrolyte, showing the highest specific capacity and Good electron ion conduction properties.
Smart Images

Figure CN119143189A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of electrochemical nanomaterial synthesis, and in particular to a method for preparing a cobalt manganese oxide material by utilizing cobalt doping to induce crystal transformation, and application thereof. Background Art
[0002] Supercapacitors are a new type of energy storage device that can be quickly charged. They have the characteristics of high power density and long cycle life. They can be used in the fields of energy storage and conversion of electric vehicles, portable electronic devices and renewable energy. Manganese is one of the more abundant metal elements on the earth, and manganese oxide is a common compound. It is often used as an electrode material for supercapacitors due to its high theoretical specific capacity, rich redox activity and easy synthesis. Compared with some rare metals or expensive materials, manganese oxide helps to reduce the manufacturing cost of supercapacitors. However, the supercapacitor performance of manganese oxide materials is far from the theoretical capacity. This is due to the low specific surface area of manganese oxide materials, poor electronic and ion conductivity, and the dissolution problem of manganese oxide electrode materials during the cycle process. In recent years, manganese oxide has been modified by morphological engineering, defect engineering and heterojunction engineering to enhance its electrochemical properties, including increasing effective active sites, intrinsic conductivity and structural stability.
[0003] In the present invention, raw materials such as manganese source and cobalt source are subjected to hydrothermal reaction. The present invention controls the crystal transformation of cobalt manganese oxide by whether to add a cobalt source and the amount of the cobalt source added. The crystal transformation is specifically Mn2O3, Mn3O4 and CoMnO3, so as to obtain spherical cobalt manganese oxide and show good supercapacitor performance, and the reduction of potassium permanganate is not involved in the reaction process, which reduces the pollution to the environment. The production process of the material of the present invention has little impact on the environment and meets the requirements of sustainable development. And the product obtained by the reaction is a micron spherical structure, the production process of the material is simple and controllable, the technology is mature, and the repeatability is strong. It can be expanded from laboratory scale to industrial scale to meet the needs of mass production. The cobalt manganese oxide obtained by this synthesis method of the present invention is of great significance because of its excellent supercapacitor performance, cost-effectiveness, simple manufacturing and less environmental harm. Summary of the invention
[0004] The object of the present invention is to provide a method for preparing a cobalt manganese oxide material by using cobalt doping to induce crystal transformation and its application, so as to solve the problems raised in the above background technology.
[0005] To achieve the above object, the present invention provides the following technical solutions:
[0006] A method for preparing a cobalt manganese oxide material by inducing crystal transformation by cobalt doping comprises the following steps:
[0007] S1. Put ethylene glycol and deionized water into a reaction container and stir to form a solution A. During the stirring process, nitrogen is introduced into the solution A to remove oxygen in the mixed solution.
[0008] S2, adding cobalt chloride hexahydrate, manganese acetate tetrahydrate, glucose-polyvinyl alcohol complex and urea to the solution A in step S1 in sequence, stirring and mixing to obtain solution B;
[0009] S3, heating the solution B obtained in step S2 to 200°C, reacting for 12 hours, cooling naturally to room temperature after the reaction is completed, centrifuging to obtain a product, washing the product with deionized water 3 times and anhydrous ethanol 3 times, and then drying the product in a drying oven at 60°C overnight to finally obtain a precursor;
[0010] S4, pouring the precursor obtained in step S3 into a crucible, placing it in a high-temperature furnace, heating it to 500° C. at a rate of 5° C. / min and maintaining it for 2 hours, then naturally cooling it to room temperature, and finally obtaining cobalt-doped manganese oxide.
[0011] Furthermore, in step S1, the mass ratio of deionized water to ethylene glycol is 1:3.
[0012] Furthermore, in step S2, the mass ratio of cobalt chloride hexahydrate, manganese acetate tetrahydrate, glucose-polyvinyl alcohol complex and urea is 1:(0.71-5.68):(0.13-1.01):(1.89-15.15), and the mass ratio of solution A in step S1 to urea in step S2 is 12:1.
[0013] Furthermore, in step S2, the mass ratio of cobalt chloride hexahydrate to manganese acetate tetrahydrate is 1:1.42.
[0014] Furthermore, the glucose-polyvinyl alcohol complex in step S2 is prepared by the following steps:
[0015] S101, adding polyvinyl alcohol to deionized water, heating to 80-95° C. to completely dissolve the polyvinyl alcohol, continuing to add glucose, p-toluenesulfonic acid and hydrochloric acid, reacting for 2-4 hours, adjusting the pH to 6-7 to obtain a mixed solution;
[0016] S102, adding 3% by mass of hydrogen peroxide to the mixed solution obtained in step S101, cooling to 65-75°C, continuing the reaction for 1-2 hours, cooling to room temperature, salting out and drying to obtain a glucose-polyvinyl alcohol complex.
[0017] Furthermore, in step S101, the concentration of p-toluenesulfonic acid is 1 mol / L, the concentration of hydrochloric acid is 4 mol / L, the mass ratio of glucose, polyvinyl alcohol and deionized water is 3:1:30, and the mass ratio of hydrochloric acid, p-toluenesulfonic acid and deionized water is 1:1:60.
[0018] Furthermore, the mass ratio between the hydrogen peroxide in step S102 and the deionized water in step S101 is 1:10.
[0019] A method for preparing a cobalt manganese oxide material by cobalt doping-induced crystal transformation is disclosed, and the cobalt manganese oxide (CoMnO3) material is prepared and used in supercapacitors.
[0020] Compared with the prior art, the present invention has the following beneficial effects:
[0021] 1. The raw materials used in the synthesis process of the present invention are safe, cheap and easy to obtain, and no harmful chemicals such as potassium permanganate are used, thereby reducing the cost of the synthesis process and its potential impact on the environment. The hydrothermal and air calcination methods do not require complex synthesis steps and additional materials, thereby reducing the cost and difficulty of preparation. The production process of the material has little impact on the environment and meets the requirements of sustainable development. The product obtained by the reaction is a micron spherical structure. The production process of the material is simple and controllable, the technology is mature, and the repeatability is strong. It can be expanded from laboratory scale to industrial scale to meet the needs of mass production.
[0022] 2. The present invention successfully induces the crystal transformation of manganese oxide in a hydrothermal reaction by using a trace amount of cobalt element. In the present invention, by doping with cobalt element, the electronic structure of manganese oxide can be changed, and its conductivity and specific capacitance can be improved. Doping can optimize the electronic structure and active sites of manganese oxide, thereby improving its capacitance performance. The synthesized manganese oxide material is a micron material, which avoids the problem that the nanostructure is easily dissolved in the electrolyte. The mass ratio of the cobalt source to the manganese source is obtained, and the synthesized cobalt manganese oxide has a perovskite structure, which is more conducive to a rapid electronic ion conduction process and exhibits the highest specific capacity;
[0023] 3. The unique six-ring structure of glucose makes the prepared nanomaterials have high nucleation quality, and the composite between glucose and polyethylene glycol has high thermal stability, which ensures the stabilizing effect of the additives. The composite material is modified on the outside of the metal to form electrostatic repulsion in the water environment, and the prepared material is dispersed stably and evenly. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 The process flow chart of synthesizing cobalt manganese oxide of the present invention is as follows;
[0025] Figure 2The process flow chart of the synthesis of the glucose-polyvinyl alcohol complex in the present invention;
[0026] Figure 3 The XRD diagrams of the corresponding products in Examples 1-3 and Comparative Examples of the present invention;
[0027] Figure 4 The comparative example CoMnO in the present invention X -0 SEM image;
[0028] Figure 5 The comparative example CoMnO in the present invention X -1 SEM image;
[0029] Figure 6 The comparative example CoMnO in the present invention X -2 SEM image;
[0030] Figure 7 The comparative example CoMnO in the present invention X -3 SEM image;
[0031] Figure 8 The cyclic voltammetry curves of CoMn2O3, CoMn3O4 and CoMnO3 in 2M KOH corresponding to the crystal forms of Examples 1-3 of the present invention are shown respectively. DETAILED DESCRIPTION
[0032] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0033] See also Figures 1 to 8 , the present invention provides a technical solution:
[0034] Example 1
[0035] A method for preparing a cobalt manganese oxide material by inducing crystal transformation by cobalt doping comprises the following steps:
[0036] S1. Put 27 g of ethylene glycol and 9 g of deionized water into a reaction vessel and stir to form a solution A. During the stirring process, nitrogen gas is introduced into the solution A to remove oxygen in the mixed solution.
[0037] S2, adding 0.198 g of cobalt chloride hexahydrate, 1.125 g of manganese acetate tetrahydrate, 0.2 g of glucose-polyvinyl alcohol complex and 3.0 g of urea to the solution A in step S1 in sequence, stirring and mixing to obtain a solution B;
[0038] S3, heating the solution B obtained in step S2 to 200°C, reacting for 12 hours, cooling naturally to room temperature after the reaction is completed, centrifuging to obtain a product, washing the product with deionized water 3 times and anhydrous ethanol 3 times, and then drying the product in a drying oven at 60°C overnight to finally obtain a precursor;
[0039] S4, pouring the precursor obtained in step S3 into a crucible, placing it in a high-temperature furnace, heating it to 500° C. at a rate of 5° C. / min and maintaining it for 2 hours, then naturally cooling it to room temperature, finally obtaining cobalt-doped manganese oxide;
[0040] The glucose-polyvinyl alcohol complex in step S2 is prepared by the following steps:
[0041] S101, adding 0.41 g of polyvinyl alcohol to 12.3 g of deionized water, heating to 90° C. to completely dissolve the polyvinyl alcohol, and then adding 1.23 g of glucose, 0.205 g of 1 mol / L p-toluenesulfonic acid, and 0.205 g of 4 mol / L hydrochloric acid, reacting for 3 h, adjusting the pH to 7 to obtain a mixed solution;
[0042] S102, adding 1.23 g of 3% hydrogen peroxide to the mixed solution obtained in step S101, cooling to 70°C, continuing the reaction for 1.5 hours, cooling to room temperature, salting out and drying to obtain a glucose-polyvinyl alcohol complex.
[0043] Example 2
[0044] A method for preparing a cobalt manganese oxide material by inducing crystal transformation by cobalt doping comprises the following steps:
[0045] S1. Put 27 g of ethylene glycol and 9 g of deionized water into a reaction vessel and stir to form a solution A. During the stirring process, nitrogen gas is introduced into the solution A to remove oxygen in the mixed solution.
[0046] S2, adding 0.792 g of cobalt chloride hexahydrate, 1.125 g of manganese acetate tetrahydrate, 0.2 g of glucose-polyvinyl alcohol complex and 3.0 g of urea to the solution A in step S1 in sequence, stirring and mixing to obtain a solution B;
[0047] S3, heating the solution B obtained in step S2 to 200°C, reacting for 12 hours, cooling naturally to room temperature after the reaction is completed, centrifuging to obtain a product, washing the product with deionized water 3 times and anhydrous ethanol 3 times, and then drying the product in a drying oven at 60°C overnight to finally obtain a precursor;
[0048] S4, pouring the precursor obtained in step S3 into a crucible, placing it in a high-temperature furnace, heating it to 500° C. at a rate of 5° C. / min and maintaining it for 2 hours, then naturally cooling it to room temperature, finally obtaining cobalt-doped manganese oxide;
[0049] The glucose-polyvinyl alcohol complex in step S2 is prepared by the following steps:
[0050] S101, adding 0.41 g of polyvinyl alcohol to 12.3 g of deionized water, heating to 80° C. to completely dissolve the polyvinyl alcohol, and then adding 1.23 g of glucose, 0.205 g of 1 mol / L p-toluenesulfonic acid, and 0.205 g of 4 mol / L hydrochloric acid, reacting for 2 h, adjusting the pH to 6 to obtain a mixed solution;
[0051] S102, adding 1.23 g of 3% hydrogen peroxide to the mixed solution obtained in step S101, cooling to 60°C, continuing the reaction for 1 hour, cooling to room temperature, salting out and drying to obtain a glucose-polyvinyl alcohol complex.
[0052] Example 3
[0053] A method for preparing a cobalt manganese oxide material by inducing crystal transformation by cobalt doping comprises the following steps:
[0054] S1. Put 27 g of ethylene glycol and 9 g of deionized water into a reaction vessel and stir to form a solution A. During the stirring process, nitrogen gas is introduced into the solution A to remove oxygen in the mixed solution.
[0055] S2, adding 1.584 g of cobalt chloride hexahydrate, 1.125 g of manganese acetate tetrahydrate, 0.2 g of glucose-polyvinyl alcohol complex and 3.0 g of urea to the solution A in step S1 in sequence, stirring and mixing to obtain a solution B;
[0056] S3, heating the solution B obtained in step S2 to 200°C, reacting for 12 hours, cooling naturally to room temperature after the reaction is completed, centrifuging to obtain a product, washing the product with deionized water 3 times and anhydrous ethanol 3 times, and then drying the product in a drying oven at 60°C overnight to finally obtain a precursor;
[0057] S4, pouring the precursor obtained in step S3 into a crucible, placing it in a high-temperature furnace, heating it to 500° C. at a rate of 5° C. / min and maintaining it for 2 hours, then naturally cooling it to room temperature, finally obtaining cobalt-doped manganese oxide;
[0058] The glucose-polyvinyl alcohol complex in step S2 is prepared by the following steps:
[0059] S101, adding 0.41 g of polyvinyl alcohol to 12.3 g of deionized water, heating to 90° C. to completely dissolve the polyvinyl alcohol, and then adding 1.23 g of glucose, 0.205 g of 1 mol / L p-toluenesulfonic acid, and 0.205 g of 4 mol / L hydrochloric acid, reacting for 4 hours, adjusting the pH to 6.5 to obtain a mixed solution;
[0060] S102, adding 1.23 g of 3% hydrogen peroxide to the mixed solution obtained in step S101, cooling to 75°C, continuing the reaction for 2 hours, cooling to room temperature, salting out and drying to obtain a glucose-polyvinyl alcohol complex.
[0061] Comparative Example
[0062] The difference between Comparative Example 1 and Example 1 is that the addition of cobalt chloride hexahydrate is omitted, and the remaining steps are exactly the same as those of Example 1.
[0063] In the present invention, Examples 1-3 used 0.198 g, 0.792 g and 1.584 g of cobalt chloride hexahydrate, respectively. The cobalt-doped manganese oxides obtained in Examples 1-3 were respectively denoted as CoMnO X -1. CoMnO X -2 and CoMnO X -3, since cobalt chloride hexahydrate was not used in the comparative example, its final product was recorded as CoMnOX-0.
[0064] Figure 3 The following are the XRD patterns of the final products obtained by adding different amounts of Co source (Examples 1-3 and Comparative Example) to the reaction. X -0 has obvious diffraction peaks at 2θ = 22.13°, 32.95°, 38.28°, 55.17°, and 65.78°, pointing to the Mn2O3 crystal form; the oxide CoMnO with a mass ratio of cobalt source to manganese source of 1:5.68 X -1 has obvious diffraction peaks at 2θ=22.12°, 32.93°, 38.21°, 49.31°, 55.14° and 65.74°, pointing to the Mn2O3 crystal form (JCPDS#71-0636). At this time, a small amount of impurity peaks point to the Mn3O4 crystal form; the oxide CoMnO with a mass ratio of cobalt source to manganese source of 1:1.42 X-2 has obvious peak diffraction peaks at 2θ=18.01°, 28.92°, 31.00, 32.38°, 36.08°, 36.49°, 38.09°, 44.41°, 50.84°, 58.50°, 59.91° and 64.61°, pointing to the Mn3O4 crystal form (JCPDS#80-0382). Compared with the pure Mn3O4 crystal form, the diffraction peak of this crystal form is shifted to the right. This is because cobalt is doped into the manganese oxide lattice, and part of the cobalt replaces the position of manganese. Since the cobalt atom is smaller than the manganese atom, the diffraction peak shifts to the right; the oxide CoMnO with a cobalt source and manganese source mass ratio of 1:0.71 X -3 has obvious diffraction peaks at 2θ=24.53°, 33.49°, 36.40°, 41.57°, 50.29°, 54.71°, 63.65° and 65.49°, pointing to the CoMnO3 crystal form (JCPDS#75-2090). At this time, a small amount of impurity peaks appear pointing to the Mn3O4 crystal form. This result shows that the crystallinity of the material changes with the change of different cobalt and manganese contents.
[0065] Figure 4 The product samples CoMnO obtained without cobalt source in the comparative example at different multiples are shown. X -0 SEM image. At low magnification, the surface of the material mainly shows a spherical structure, and at high magnification, it can be found that the surface of the sphere is composed of particles, and the particles are evenly distributed.
[0066] Figure 5 The product samples CoMnO obtained with the participation of cobalt source in Example 1 at different magnifications are shown. X -1 SEM image. At low magnification, the material surface mainly shows a spherical structure, and at high magnification, it can be found that the surface of the sphere is composed of particles, and the particles are evenly distributed.
[0067] Figure 6 The product samples CoMnO obtained with the participation of cobalt source in Example 2 at different magnifications are shown. X -2 SEM image. At low magnification, the surface of the material mainly shows a spherical structure, and at high magnification, it can be found that the surface of the sphere is composed of particles, and the particles are evenly distributed.
[0068] Figure 7 The product samples CoMnO obtained with the participation of cobalt source in Example 3 at different magnifications are shown. X -3 SEM image. At low magnification, the surface of the material mainly shows a spherical structure, and at high magnification, it can be found that the surface of the sphere is composed of particles, and the particles are evenly distributed.
[0069] pass Figure 4-7It can be seen from the displayed results that the material surface of the nanoparticles prepared by the hydrothermal method in the present invention mainly exhibits a spherical structure at low magnification, and it can be found at high magnification that the surface of the sphere is composed of particles, and the particles are evenly distributed, which proves that the glucose-polyvinyl alcohol complex used in the present invention can effectively ensure that the prepared micron particles are evenly distributed and have an excellent nucleation effect.
[0070] Electrochemical performance test:
[0071] The prepared cobalt manganese oxide materials were subjected to three-electrode electrochemical tests using an electrochemical workstation. The reference electrode was Hg / HgO (2 mol / L KOH), the counter electrode was made of a platinum sheet or a platinum mesh, the working electrode was a nickel foam containing active materials fixed by a platinum electrode, and the electrolyte was a 2 mol / L potassium hydroxide solution. The charge storage mechanism of the three cobalt manganese oxide materials can be determined by the cyclic voltammetry test curves. In this experiment, the cyclic voltammetry test voltage ranged from -0.2 V to 0.6 V, and the scan rate was 20 mV s -1 . Figure 8 CoMnO X -1. CoMnO X -2 and CoMnO X The cyclic voltammetry curves of cobalt-doped Mn2O3, cobalt-doped Mn3O4 and cobalt-doped CoMnO3 corresponding to the -3 material. According to the shape of their cyclic voltammetry curves, a pair of obvious redox peaks appear. This result shows that the energy storage mechanism of the prepared cobalt manganese oxide follows the pseudocapacitive mechanism. The redox peaks come from the rapid redox reaction on the surface of the electrode material.
[0072] The specific capacities of three manganese oxide materials with different ratios can be calculated based on the cyclic voltammetry curves, with a scan rate of 20 mV s -1 The specific capacities of cobalt-doped Mn2O3, cobalt-doped Mn3O4 and cobalt-doped CoMnO3 materials are 241, 218 and 442 F / g respectively. The cobalt manganese oxide obtained when the mass ratio between cobalt chloride hexahydrate and manganese acetate tetrahydrate is 1:1.42 has the highest specific capacity. This is because the CoMnO3 material formed at this time has a perovskite structure, which is more conducive to the rapid electron ion conduction process.
[0073] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing cobalt manganese oxide material by using cobalt doping to induce crystal transformation, characterized in that: The steps include: S1. Put ethylene glycol and deionized water into a reaction container and stir to form a solution A. During the stirring process, nitrogen is introduced into the solution A to remove oxygen in the mixed solution. S2, adding cobalt chloride hexahydrate, manganese acetate tetrahydrate, glucose-polyvinyl alcohol complex and urea to the solution A in step S1 in sequence, stirring and mixing to obtain solution B; S3, heating the solution B obtained in step S2 to 200°C, reacting for 12 hours, cooling naturally to room temperature after the reaction is completed, centrifuging to obtain a product, washing the product with deionized water 3 times and anhydrous ethanol 3 times, and then drying the product in a drying oven at 60°C overnight to finally obtain a precursor; S4, pouring the precursor obtained in step S3 into a crucible, placing it in a high-temperature furnace, heating it to 500° C. at a rate of 5° C. / min and maintaining it for 2 hours, then naturally cooling it to room temperature, and finally obtaining cobalt-doped manganese oxide.
2. The method for preparing cobalt manganese oxide material by cobalt doping-induced crystal transformation according to claim 1, characterized in that: The mass ratio of deionized water to ethylene glycol in step S1 is 1:
3.
3. The method for preparing cobalt manganese oxide material by cobalt doping-induced crystal transformation according to claim 1, characterized in that: The mass ratio of cobalt chloride hexahydrate, manganese acetate tetrahydrate, glucose-polyvinyl alcohol complex and urea in step S2 is 1:(0.71-5.68):(0.13-1.01):(1.89-15.15), and the mass ratio of solution A in step S1 to urea in step S2 is 12:
1.
4. The method for preparing cobalt manganese oxide material by cobalt doping-induced crystal transformation according to claim 1, characterized in that: The mass ratio of cobalt chloride hexahydrate to manganese acetate tetrahydrate in step S2 is 1:1.
42.
5. The method for preparing cobalt manganese oxide material by cobalt doping-induced crystal transformation according to claim 1, characterized in that: The glucose-polyvinyl alcohol complex in step S2 is prepared by the following steps: S101, adding polyvinyl alcohol to deionized water, heating to 80-95° C. to completely dissolve the polyvinyl alcohol, continuing to add glucose, p-toluenesulfonic acid and hydrochloric acid, reacting for 2-4 hours, adjusting the pH to 6-7 to obtain a mixed solution; S102, adding 3% by mass of hydrogen peroxide to the mixed solution obtained in step S101, cooling to 65-75°C, continuing the reaction for 1-2 hours, cooling to room temperature, salting out and drying to obtain a glucose-polyvinyl alcohol complex.
6. The method for preparing cobalt manganese oxide material by using cobalt doping to induce crystal transformation according to claim 5, characterized in that: In step S101, the concentration of p-toluenesulfonic acid is 1 mol / L, the concentration of hydrochloric acid is 4 mol / L, the mass ratio of glucose, polyvinyl alcohol and deionized water is 3:1:30, and the mass ratio of hydrochloric acid, p-toluenesulfonic acid and deionized water is 1:1:
60.
7. The method for preparing cobalt manganese oxide material by using cobalt doping to induce crystal transformation according to claim 5, characterized in that: The mass ratio of the hydrogen peroxide in step S102 to the deionized water in step S101 is 1:
10.
8. Use of the cobalt manganese oxide material prepared by the method for preparing cobalt manganese oxide material by cobalt doping-induced crystal transformation as claimed in any one of claims 1 to 7 in supercapacitors.
